Respuesta :

Number 2 is the answer););!;!:!;!;!;!;!;!;!;!;!;?;

Answer:

2nd option; [tex]c=9-a+b[/tex]

Step-by-step explanation:

  1. The first thing you need to do, is rewrite the equation without the square root.
  2. So for instance [tex]\sqrt{16}=4[/tex] and [tex]16=(4)^2[/tex] therefore [tex]a-b+c=(3)^2[/tex]
  3. Then [tex]a-b+c=9[/tex]
  4. Now we take away ' [tex]a[/tex] ' on both sides and add ' [tex]b[/tex] ' on both sides
  5. So [tex]a-(a)-b+(b)+c=9-(a)+(b)[/tex]
  6. Which gives us [tex]0+0+c=9-a+b[/tex] which is simply [tex]c=9-a+b[/tex]

Hope this helps